Local Sourcing in the Cabo Verde Tourism Food Supply Chain : Opportunities and Challenges - World Bank Group (World Bank, Washington, DC, 2020)
The objective of this research report is to assess the market potential for local sourcing in the Cabo Verde tourism food supply chain, with a particular emphasis on traditional sectors such as agriculture and fisheries. As tourism continues to expand rapidly in Cabo Verde, the sector creates a growing market potential for locally sourced produce. The number of inbound tourists in the country has steadily increased from 428,000 in 2011 to 710,000 in 2018 - a 7,5 percent CAGR in the period - causing with it a rise in the direct economic contribution of travel & tourism activities to GDP, now estimated at near 20 percent. The islands of Sal and Boa Vista dominate the market, attracting together 76,4 percent of all arrivals, who visit overwhelmingly under the all-inclusive resort segment. In addition, higher average lengths of stay in these two islands imply that they account for proportionally more room nights (89,9 percent of the total bed nights) than the rest of the country. The level of linkages between the primary sector and tourism has long been a debated topic, particularly the untapped potential of additional positive spillovers and impact on poverty reduction. A World Bank study commissioned in 2013 estimated that more than 80 percent of food and beverage products consumed by all-inclusive resorts were imported. While these resorts have been decisive in pushing infrastructure development and promoting job creation, the level of linkages with local businesses is seen as being below potential. The study found that the low level of local food sourcing stemmed from a range of challenges related to sanitary and quantity standards, volumes, reliability of supply, and connectivity. Since then, very little research has sought to quantify the market potential in supplying tourism or assessing which products could be prioritized at local production level, on comparative and competitive advantages vis-à-vis imports. The methodology for this research comprised a quantitative and qualitative survey with a representative sample of large hotels in Sal and Boa Vista, in addition to in-depth follow-up interviews and desk review of pertinent data. The type of commercially sensitive information required from the surveyed participants severely undermined participation, despite guarantees of confidentiality. A substantial effort was invested in following-up, and the team was able to gather consumption data covering a small representative sample of large hotels, as well as relevant information on market characteristics and trends from the leading hotel supplier wholesalers.